The incidence of lambliasis among school children in Cairo - Boutros, Naguib Zaki (The Turkish Journal of Pediatrics, 1962)
Lamblia infection among school children in Cairo was studied in two seasons: summer and winter. The incidence of infection was found to be higher in summer than in winter for obvious reasons. The comparative study of the incidence of Lamblia and Endamoeba infections showed that Lamblia infection is almost as prevalent as Endamoeba infection during the summer time and has more than half the incidence of Endamoeba infection during the winter time. Mixed infection by both parasites is a possibility. The possibility of Lamblia sharing with Endamoeba in causing intestinal trouble in our children is now to be kept in mind. A trial on a small scale of drugs other than Atabrine was made. Nivaquin was found to be a new and a better weapon to eradicate this infection.